Footwear used by older people and a history of hyperkeratotic lesions on the foot: A prospective observational study. Issue 15 (April 2017) - Palomo-López, Patricia; Becerro-de-Bengoa-Vallejo, Ricardo; Losa-Iglesias, Marta Elena; Rodríguez-Sanz, David; Calvo-Lobo, César; López-López, Daniel
Abstract : Abstract: Inadequate footwear, painful and hyperkeratotic lesions (HL) are an extremely common problems amongst older people. Such problems increase the risk of falls, hamper mobility, reduction of quality of life, dignity, and ability to remain independent. The etiology of painful and feet conditions is poorly understood. To discover footwear preferences of older people, pain tolerance may favor presence of HL for the use of inadequate footwear in old age. A sample of 100 participants with a mean age of 74.90 ± 7.01 years attended an outpatient clinic where self-reported demographic data, frequency with which they checked their feet were recorded and measurements were taken of foot sensitivity. Additionally, all participants' shoes were allocated into optimal, adequate, and dangerous categories based on design, structural and safety features, and materials. Only 12% of the sample population checked their feet every day, 37% revealed symptoms of neuropathy, 14% used optimal shoes, and 61% presented HL. In a bivariate analysis, no significant differences were observed. HL are associated with inadequate footwear, loss of sensitivity, and low frequency of foot health checks.